Możliwości zróżnicowania źródeł przychodów Lasów Państwowych w Polsce - Lotz, Danuta; Jodłowski, Krzysztof; Kocel, Janusz (Leśne Prace Badawcze, 2025)
In Poland, the share of forest districts’ revenues from timber sales between 2005 and 2015 in the State Forests National Forest Holding (PGL LP) was 84 to 87 per year. However, forest management should be carried out in a sustainable manner n order to achieve a variety of economic, environmental and social benefits. Therefore, diversification of revenue sources should be sought, which also helps to spread financial risks and maintain high economic potential. The aim of the study was to determine the nature of the activities and the extent of diversification of revenues from sources other than timber sales at PGL LP. The study covered the revenues of all (430) forest districts in relation to 11 groups of non-timber revenue activities from 2005-2015. Statistical methods were used to analyse the diversification of forest districts and identify groups that are similar in to all non-timber revenue activities. This was the first comprehensive study of its kind conducted in Poland. For the calculation of profitability, activities not related to the sale of timber were categorised into three groups: Activities that forest districts should (1) develop in the future to reduce financial risks, among others; (2) reduce; (3) hand over to private companies (outsourcing), whose activities should be supported by creating of appropriate instruments. This group should also include the activities of the State Forests, which do not represent any significant competition for the private sector, but are of non-economic importance, especially in terms of public relations (PR). In 2015, all forest districts generated on average the largest other operating revenues in the amount of PLN = 0.51 million, which, however, should not be developed due to their instability. These are revenues that are not directly related to the ordinary activities of the forest districts (e.g. revenues from the sale of fixed assets, from compensation and penalties, subsidies from the European Union for meadow and agricultural management carried out by the forest districts). The areas of activity to be developed include other sales revenues (mainly lease of land, ponds, lakes and fixed assets) PLN = 0.27 million, basic revenues (excluding revenues from the sale of timber), i.e. revenues from the sale of cones and seeds and seedlings, and subsidies from the European Union for basic activities PLN = 0.25 million. On average, the forest districts generated the highest revenues from other sales, which are independent of other activities and help to spread the economic risk of the forest districts. One activity with strong revenue fluctuations is social and welfare activity, which the forest districts should gradually reduce. In 2015, all forest districts had a high fluctuation range of revenue from auxiliary activities CV = 882% and core activities (excluding timber) CV = 392% and a low fluctuation range of revenue from financial activities CV = 48%. The State Forests should include the question of each forest district’s income from sources other than timber sales in the process of continuous in-depth analysis in order to maintain their financial stability.